Colorectal cancer treated by resection and extended lymphadenectomy: patterns of spread in left‐ and right‐sided tumours. Issue 8 (4th April 2020) - Kataoka, K.; Beppu, N.; Shiozawa, M.; Ikeda, M.; Tomita, N.; Kobayashi, H.; Sugihara, K.; Ceelen, W.
Abstract : Background: Whether tumour side affects the anatomical extent and distribution of lymph node metastasis in colon cancer is unknown. The impact of tumour side on the anatomical pattern of lymphatic spread in colon cancer was assessed. Methods: Patients with stage III colon cancer from a Japanese multi‐institutional database who underwent extensive (D3) lymphadenectomy, which is similar in concept to complete mesocolic excision with central venous ligation, were divided into groups with right‐ and left‐sided tumours. Based on location, mesenteric lymph nodes were categorized as paracolic (L1), intermediate (L2) or central (L3). The Kaplan–Meier method was used to evaluate disease‐free survival (DFS) and overall survival (OS), and multivariable Cox models were used to evaluate the association between anatomical lymph node level, metastatic pattern and outcome. Results: A total of 4034 patients with stage III colon cancer (right 1618, left 2416) were included. Unadjusted OS was worse in patients with right colon cancer (hazard ratio 1·23, 95 per cent c.i. 1·08 to 1·40; P = 0·002), but DFS was similar. Right‐sided tumours more frequently invaded L3 nodes than left‐sided lesions (8·5 versus 3·7 per cent; P < 0·001). The proportion of patients with a skipped pattern of lymphatic spread was higher in right than in left colon cancer (13·7 versus 9·0 per cent; P < 0·001). In multivariable analysis, invasion of L3 nodes was associated with worse OS in left but not in right colon cancer. The presence of skipped metastasis was associated with worse DFS in left, but not right, colon cancer. Conclusion: There are significant differences in the pattern of lymph node invasion between right‐ and left‐sided stage III colon cancer, and in their prognostic significance, suggesting that tumour side may dictate the operative approach. Abstract : After adjustment for age, sex, pT category, tumour size, pattern of lymph node metastasis and lymph node ratio, overall survival was nearly identical in right colon cancer with invaded L2 or L3 nodes. In left colon cancer, however, overall survival was worse in L3‐positive compared with L2‐positive colon cancer. Right versus left‐sided lymphatic drainage in colon cancer Abstract : Antecedentes: Se desconoce si la lateralidad del tumor influye en la extensión anatómica y en la distribución de las metástasis en los ganglios linfáticos ( lymph node metastasis, LN) en el cáncer de colon. Se evaluó el impacto de la lateralidad del tumor en el patrón anatómico de diseminación linfática en el cáncer de colon. Métodos: Los pacientes con cáncer de colon en estadio III recogidos en una base de datos japonesa multicéntrica, que se sometieron a una linfadenectomía ampliada (D3), conceptualmente similar a la escisión completa del mesocolon con ligadura venosa central, se dividieron en cáncer de colon del lado derecho y cáncer de colon del lado izquierdo. Según la ubicación, las LN mesentéricas se clasificaron como paracólicas (L1), intermedias (L2) o centrales (L3). Se utilizó el método de Kaplan‐Meier para evaluar la supervivencia libre de enfermedad ( disease‐free survival, DFS) y la supervivencia global ( overall‐survival, OS), y se utilizaron modelos de Cox multivariados para evaluar la asociación entre el nivel L y el patrón metastásico con el resultado. Resultados: Se incluyeron 4.034 pacientes con cáncer de colon en estadio III (cáncer de colon derecho: n = 1.618, cáncer de colon izquierdo: n = 2.416). La OS no ajustada fue peor en el cáncer de colon derecho (cociente de riesgos instantáneos, hazard ra tio, HR 1, 23, i.c. del 95%: 1, 08‐1, 4; P = 0, 002), pero la DFS fue similar. La afectación de los ganglios L3 fue más frecuente en pacientes con cáncer de colon derecho que izquierdo (8, 5% versus 3, 7%, P < 0, 001). En el cáncer de colon derecho, la proporción de pacientes con patrón de diseminación linfática discontinuo, con salto entre niveles, fue mayor en comparación con el cáncer de colon izquierdo (13, 7% versus 9%; P < 0, 001). En el análisis multivariante, la invasión de los ganglios L3 se asoció con una peor OS en el cáncer de colon izquierdo, pero no en el cáncer de colon derecho. La presencia de metástasis discontinuas se asoció con una peor DFS en el cáncer de colon izquierdo, pero no en el cáncer de colon derecho. Conclusión: Existen diferencias significativas en el patrón de invasión de los LN entre el cáncer de colon derecho e izquierdo en estadio III, así como en su importancia pronóstica, lo que sugiere que la lateralidad del tumor puede determinar el abordaje quirúrgico.